Gelastic seizures with dancing arising from the anterior prefrontal cortex. Issue 2 (June 2014) - Neilson, John; Snyder, Tom; Pugh, Jeff; Wheatley, Matt; Tang‐Wai, Richard
<x xml:space="preserve">Abstract</x> Aim. This case report provides insight into the function of the anterior prefrontal cortex (aPFC), specifically Brodmann Area 10 (BA10), and its interconnectivity. Method. We present a 10‐year‐old patient with lesional epilepsy and ictal onset, localised to BA10 in the aPFC. Results. Thirty‐four seizures were recorded. All seizures involved a demonstration of elation with laughter that was associated with a variety of different patterns of complex motor behaviour that included performing specific celebratory movements and acting out a Michael Jackson dance move. Electrographically, the seizures were all stereotyped and arose from the right frontal region, followed by a distinct left temporal ictal rhythm that corresponded with the onset of the behaviours. The lesion in the right aPFC was identified as a mixed lesion with both dysembryoplastic neuroepithelial tumour cells and type II cortical dysplasia. Conclusion. The electrographic analysis and unique seizure semiology suggest a connection between the aPFC and the contralateral temporal lobe. This neural pathway appears to be involved in the activation of previously formed procedural memories, creating an intensely positive emotional experience.